2017
DOI: 10.1111/jeb.13079
|View full text |Cite
|
Sign up to set email alerts
|

Signals of selection in conditionally expressed genes in the diversification of three horned beetle species

Abstract: Species radiations may be facilitated by phenotypic differences already present within populations, such as those arising through sex-specific development or developmental processes biased towards particular reproductive or trophic morphs. We sought to test this hypothesis by utilizing a comparative transcriptomic approach to contrast among- and within-species differentiation using three horned beetle species in the genus Onthophagus. These three species exhibit differences along three phenotypic axes reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Polyphenism denotes that multiple phenotypes are produced by a single genotype due to environmental induction (Ogawa and Miura 2014). This phenomenon exists commonly in organisms, especially in insects, such as castes in social insects, gregarious and solitary change of locusts, seasonal morphs of butterflies, and sexually selected phenotypes in beetle horns (Corona et al 2016;Klein et al 2016;Pespeni et al 2017;Wang et al 2014). Of the various phenotypes observed in the complex life cycle of aphids, the wing polyphenism seen in most species is conspicuous (Ogawa and Miura 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenism denotes that multiple phenotypes are produced by a single genotype due to environmental induction (Ogawa and Miura 2014). This phenomenon exists commonly in organisms, especially in insects, such as castes in social insects, gregarious and solitary change of locusts, seasonal morphs of butterflies, and sexually selected phenotypes in beetle horns (Corona et al 2016;Klein et al 2016;Pespeni et al 2017;Wang et al 2014). Of the various phenotypes observed in the complex life cycle of aphids, the wing polyphenism seen in most species is conspicuous (Ogawa and Miura 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, this result may be a consequence of assessing gene expression based on whole‐body RNA extractions. Gene expression in O. taurus , like most organisms, is highly tissue‐specific (Pespeni et al, 2017; Snell Rood et al, 2010). RNA extractions for the present study included the entire head and thorax for larvae and prepupae and whole bodies for pupae and adults—a design chosen to maximize sequencing coverage across the whole transcriptome to be able to generate SNP and expression data for as many genes as possible.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, genes that are expressed in a context‐dependent manner have reduced pleiotropic constraint and thus may be well‐positioned to contribute to the early stages of population adaptation to novel conditions via modifications of their regulation (Hunt et al, 2011; Moczel et al, 2014; Snell Rood et al, 2010). Indeed, several studies have identified signatures of rapid divergence between species in conditionally expressed genes, such as sex‐biased genes in Drosophila melanogaster (Perry et al, 2014), and tissue‐ and sex‐specific genes in horned beetles (Pespeni et al, 2017; Snell Rood et al, 2010; Warren et al, 2014). However, few studies have taken advantage of recent population colonizations to assess potential relationships between geographic variation in allele frequencies and context‐dependent gene expression and its evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which climatic changes cause plastic adjustments, and the relative importance of plasticity compared to other responses such as migration or evolution, are still debated (Merilä and Hendry 2014). While plasticity is ubiquitous, the extent to which plasticity is adaptive and evolving under selection is poorly understood (Arnold et al, 2019;Dudley and Schmitt, 1996;Hamann et al, 2016;Nussey et al, 2005;Pespeni et al, 2017;Saltz et al, 2018;Sultan, 2004;Van Buskirk and Steiner, 2009;Via et al, 1995), and whether plasticity is costly is also contentious (Auld et al, 2010). responses follow the same or opposite directions as selection on baseline expression-i.e., cogradient or counter-gradient selection sensu Byars and colleagues (2007).…”
Section: Main Text Introductionmentioning
confidence: 99%